Plants New to India - Deb, D. B. (Indian Forester, 1965)
The present paper records for India, from North East Frontier Agency, three taxa originally collected from Yunnan, China. The taxa are: (1) Bulleyia yunnanensis Schltr. (Orchidaceae), (2) Cardamine scoriarum W. W. Smith (Cruciferae) and (3) Primula euosma Craib (Primulaceae). Further the paper records Cardamine scoriarum W.W. Smith for Burma also. Two of the taxa were collected by the author himself.